Pengaruh Model Pembelajaran Discovery dan Gaya Kognitif Siswa Terhadap Kemampuan Berpikir Kritis Matematika Siswa Kelas VIII SMP Negeri 24 Kerinci - Lismayani Lismayani (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to know the effect of Discovery learning mode toward and student critical Thinking Skills in mathematics, the effect of students’ cognitive style toward student critical Thinking Skills in mathematics the interaction effect between learning mode and students’ cognitive style toward student critical Thinking Skills in mathematics at student grade VIII (Eight) SMP Negeri 24 kerinci academic year 2022/2023. The resarch conducted by using quasy experimental design research method follows nonequivalent control group design version by implementing factorial design 2 × 2. The population of the research are students of SMP Negeri 24 Kerinci grade VIII even term academic year 2022/2023. The research’s sample determined randomly, consists of experimental class in ammount 23 students and control class in ammount 24 students. The data collection conducted using two kind of instruments Group Embedded Figures Test (GEFT) to measure students’ cognitive style and instrument students’ critical Thinking Skills in mathematics in the form of essay. The research hypotheses is tested by using Two Way Anova, after pre-requirment has been fulfilled, which are the normality of data distribution and the homogenity of variant among sample. Result data analysis and statistical testing show that discovery learning mode take effect toward Higher Order Thinking Skills, students’ cognitive style take effect toward student critical Thinking Skills in mathematics, There is no interaction between learning mode and students’ cognitive style toward students’ student critical Thinking Skills in mathematics. Based on the results of this study it is suggested to the teachers, particularly the mathematics teacher that the implementation of the discovery learning model can be developed as an innovation in teaching and learning process.